Drug Utilization Pattern Among COVID-19 Patients in A Tertiary Care Centre: An Observational Study - Dr. Ramya Rachamanti; Dr Rajesh Dupaguntla; Dr Solomon Raju. K (International Journal of Pharma and Bio Sciences, 2023)
Drug utilization study was defined by the World Health Organization as the study of marketing, distribution, prescription, and use of drugs in a society, with special emphasis on medical, social, and economic consequences. The coronavirus disease 2019 (COVID-19) outbreak has quickly swept across the world and has been declared a Public Health Emergency of International Concern. There were 4.47 crores of COVID-19 cases in India, with 5.3 lakhs of deaths as of Dec 23, 2022. However, only a few studies evaluated the pattern of use of drugs among patients with COVID-19 in India. Hence, the current study analyzed the drug utilization pattern among COVID-19 patients at our tertiary care center (GMC/GGH) in Ongole, Andhra Pradesh, India. It is an observational, retrospective study. Case records of 100 patients coming to OP or admitted at our tertiary care center with COVID-19 from March to December 2021 were taken as the study sample. Fifty patients belonged to group A (asymptomatic and mild COVID-19 and 50 patients belonged to group B (moderate and severe COVID-19). Drug utilization pattern was assessed using the World Health Organization indicators. A total of 859 drugs were prescribed for 100 patients. Among them, 249(28.9%) were antibiotics. 219(25%) were injections. 678(78.9%) were prescribed in generic names, and 745(81%) drugs were prescribed from the national list of essential medicines of 2022. There is a significant difference in all 5 WHO indicators between groups A and B. There is a knowledge gap in many drugs used to treat COVID-19. Evidence-based pharmacotherapy for patients with COVID-19 is vital to enhance valuable healthcare resources during the pandemic. The information derived from this research work will be handed over to the stakeholders for implementing modifications wherever needed to improve clinical outcomes.